SITUATIONAL LEADERSHIP IN THE CONTEXT OF GLOBAL ENTREPRENEURIAL BUSINESS: EFFECTIVE COMMUNICATION STRATEGIES FOR ADDRESSING ENVIRONMENTAL CHANGES - Sutrisno; Suherlan; Murthada (Technopreneurship and Educational Development Review (TENDER), 2024)
The current global business environment is highly dynamic and fraught with uncertainty. Globalization, technological advancements, and rapid economic changes compel companies to continually adapt. Situational leadership is crucial as it enables leaders to adjust their leadership styles according to the situation and organizational needs. This research aims to explore and analyze the effectiveness of situational leadership in the context of global entrepreneurial business, with a specific focus on the communication strategies employed to tackle environmental changes. This study utilizes a literature review method with a qualitative approach. Data were gathered from articles accessed via Google Scholar published between 1988 and 2024. The study findings indicate that situational leadership offers an adaptive and effective approach in addressing the complexities of the global business environment. By tailoring leadership styles to specific situations, leaders can achieve maximum effectiveness in guiding teams and managing change. Effective communication strategies such as transparency, regular feedback, active listening, and leveraging technology support the successful implementation of situational leadership. By proactively preparing and managing change effectively, leaders can ensure that their organizations remain competitive in facing global business challenges.